A comparative study on the efficacy of kirschner wire tension band combined with anchor cross-suture internal fixation versus partial patellectomy in the treatment of comminuted inferior pole patellar fractures - Siyu Duan; Rongda Xu; Hanfei Liu; Ming Sun; Hairui Liang; Zhencun Cai (BMC Musculoskeletal Disorders)
Abstract Objective The treatment of comminuted inferior pole patellar fractures has long posed a challenge for orthopedic surgeons. This study aims to compare the biomechanical stability and clinical efficacy of Kirschner wire tension band combined with anchor cross-suture fixation versus traditional partial patellectomy in the treatment of comminuted inferior pole patellar fractures. Methods A retrospective analysis was conducted on 14 patients who underwent Kirschner wire tension band combined with anchor cross-suture fixation (Group A) in our department of orthopedics from September 2020 to April 2022. Additionally, we matched 14 patients with similar baseline characteristics who received inferior pole patellectomy combined with patellar tendon repair (Group B). The two groups were compared in terms of operative time, intraoperative blood loss, postoperative complications, and at the final follow-up, knee range of motion (ROM), visual analogue scale (VAS) score, Bostman knee function score, peak knee torque, and Insall-Salvati (IS) ratio. Results All patients were followed up for more than 12 months. At the final follow-up, Group A showed significantly better outcomes than Group B in terms of knee range of motion (ROM), Bostman knee function score, knee VAS score, and average peak knee torque, with statistically significant differences (P < 0.05), indicating faster postoperative recovery and better clinical results in Group A. The IS ratio of the injured knee in Group B was 0.71 ± 0.66, less than 0.8, suggesting a decrease in patellar height. There were no significant differences between the two groups in terms of operative time, intraoperative blood loss, or incision length (P > 0.05). In Group A, one patient experienced complications from hardware irritation, while in Group B, one patient had postoperative knee pain, and two patients experienced knee extension weakness after cast removal and rehabilitation. Conclusion Kirschner wire tension band combined with anchor cross-suture fixation for the treatment of inferior pole patellar fractures yields satisfactory results. This technique provides reliable fixation, restores the original extensor mechanism, promotes early postoperative rehabilitation, and reduces the incidence of complications, making it suitable for clinical application and widespread use. Evidence level Level III (retrospective comparative study)